Endurance Profile of Fik Students of Class Ikor-E 22 with Bleep Test - Mawardinur, Mawardinur; Sitanggang, Indah Swira; Zalukhu, Intan Kartika F; Sipayung, Cindy Vini Rosen; Siregar, Alpina Damayanti; Gultom, Jonatan (Journal Coaching Education Sports, 2025)
Endurance is closely related to daily human activities or work in doing work or moving. The purpose of this study was to determine the results of physical fitness measurements of endurance of students of the sports science program, class Ikor E 2022 using the Bleep Test. To determine the level of cardiorespiratory endurance or VO2max using the Bleep test. The research method used is descriptive quantitative (percentage). The population in this study were UNIMED Sports Science students of IKor E class 2022 totaling 26 people where 19 were male and 7 were female. The results showed that of the 26 Sports Science students there were 1 person or 2.6% of the physical fitness level in the very poor category, 3 people or 8% of the physical fitness level in the very poor category, 13 people or 50% of the physical fitness level in the sufficient category, 8 people or 36.8% of the physical fitness level in the good category, 1 person or 2.6% of the physical fitness level in the very good category. Based on the results of this study, it can be concluded that the level of physical fitness, especially cardiorespiratory endurance, of UNIMED's athletic science study program students in Ikor E Class 2022 is in the sufficient category.